The Influence of Smartphone Use and Digital Interaction on Alone Together Behavior Among University Students - Meydi Villareal , Daniel; Hakim, Muhammad Lukman; Setiawan , Fajar Alif; Koga, Yohanes; Albar, Zainuddin Amriti (oneamd.com, 2025)
The rapid development of digital communication technology has significantly transformed social interaction patterns, particularly among university students who are active smartphone users. Although smartphones facilitate instant communication and access to information, excessive use may lead to social alienation despite physical togetherness, a phenomenon known as alone together. This study aims to analyze the influence of smartphone use and digital interaction on alone together behavior among university students. The research employed a quantitative approach using a descriptive-correlational method. Data were collected through an online questionnaire distributed to 121 university students in Malang City. The variables examined were smartphone use, digital interaction, and alone together behavior. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, Ftest, and coefficient of determination (R²). The results indicate that smartphone use has a positive and significant effect on alone together behavior. Digital interaction also shows a positive and significant influence and is the most dominant variable affecting alone together behavior. Simultaneously, smartphone use and digital interaction significantly influence alone together behavior among students. This study concludes that high dependence on smartphones and intensive digital interaction contribute to decreased quality of face-to-face social interaction. Therefore, balancing digital communication and direct interpersonal interaction is essential to maintain students’ social and emotional well-being.